(untitled) (Informatica, 2025)
In modern police command activities, the requirements for the combat effectiveness of weapons and equipment are getting higher and higher, and the demand for equipment use is also expanding. Become an integral part of the policing decision support system. The system mainly realizes the human-computer interaction of shooting training. Through the programming threshold segmentation and affine transformation technology, the shooting scenes with different effects at different positions are simulated within the target threshold range, and the distance and speed parameters are set according to the needs, which are obtained through the step calculation algorithm. The possible motion of each point at this time is converted into an image sequence for storage. Finally, by calculating the training results, the shooting scene is simulated, and according to the simulated motion, the appropriate thresholds and thresholds for parameters such as distance and speed are selected. Several computational experiments and user studies were used to verify the system’s efficiency. The findings show a notable enhancement in shooting accuracy and decisionmaking speed, with an average accuracy increase of 5% compared to conventional techniques. User feedback validated the system’s ability to simulate real-world shooting scenarios, presenting a useful tool for improving police training programs. Furthermore, the system showed an optimal threshold determination procedure for important parameters, which enhanced the training experience. These results highlight the system’s importance in the advancement of police training technologies